Penggunaan NRF24L01 Untuk Monitoring Data Pada PLTS Kapasitas 309 WP - Budiono, Berliano; B Sulistiawati, Irrine; Agustini, Ni Putu (FORTEI (Forum Pendidikan Tinggi Teknik Elektro Indonesia), 2023)
To obtain renewable energy, there are obtaining electricity supply it can be done by utilizing solar energy radiation power. With using solar cells to convert solar energy into electrical energy, or we call as Solar Power Plants (PLTS). This research will develop previous research, there are the design of output monitoring systems and data recording on Arduino microcontroller-based solar panels where tools designed to monitor current, voltage and light intensity use the NRF24l01 module remotely to facilitate analysis of solar cells using the Arduino Uno microcontroller system. Data processing taken in seconds and minutes is displayed on a PC or smartphone screen using Blynk software and the data is stored on the PLX-DAQ in real time. so that researchers do not need to observe PLTS in place for data collection because the tool can cover it automatically with an error rate of sensor testing used less than 5%.